HIV prevalence, sexual behaviours and engagement in HIV medical care among an online sample of sexually active MSM in Venezuela. - Perez-Brumer, Amaya G; Oldenburg, Catherine E; Biello, Katie B; Novak, David S; Rosenberger, Joshua G; Mimiaga, Matthew J (International journal of STD & AIDS, 2015)
In Venezuela, members of a social and sexual partner-networking site for MSM completed an online survey regarding sexual behaviours and HIV medical care. Among the 2851 respondents, self-reported HIV prevalence was 6.6%. Of participants living with HIV, 73.2% reported taking antiretroviral medication and, 56.6% reported complete adherence within the past month. Participants living with HIV were more likely to be older (aOR = 1.04 per one-year increase in age, 95% CI: 1.02, 1.06) and diagnosed with an STI in the previous year (aOR 3.26, 95% CI: 2.11, 5.04). These data provide further understanding of the HIV epidemic among MSM in Venezuela, and potential targets for HIV prevention interventions.